KINERJA KARYAWAN ALTIS PRODUCTION DIPENGARUHI SEMANGAT KERJA DAN DISIPLIN KERJA - Wasis Wasis (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The purpose of this study is to find out whether there is an influence of morale on employee performance in Altis Production as well as to find out whether there is an influence of work discipline on employee performance at Altis Production. This study used explanatory research. For this research instrument is a questionnaire using a likert scale. The object of research to be studied is Altis Production employees with 42 samples used, the sample technique that will be used for sampling is a saturated sample. The analysis method to be used is multiple linear regression analysis. The R2 Square value of 0.472 means that morale and work discipline play a good role in influencing employee performance at Altis Production by 47.2% The results of the study concluded that high morale can improve the performance of Altis Production employees. High Work Discipline can improve the performance of Altis employees.